Public Perception on Stock Price Determinants and their Effect of Listed Banks and Finance Companies in Nepal - Ram Chandra Bhandari; Alok Kumar; Surender Kumar Gupta; Rajan Bikram Thapa; Asha Acharya (Utilitas Mathematica, 2025)
Research on Public Perception on Stock Price Determinants and Their Effect of Listed Banks and Finance companies in Nepal has the specific objective of identifying stock price determinants of listed banks and finance companies and their effect on the price. Simplification of the specific objective into elementary objectives assists identification, and assessment of the effect. The integration of pragmatism research philosophy, exploratory sequential mixed research design is the foundation of this research. The researcher has used focus group discussion and sample survey for the primary data collection with a stratified random sampling procedure. The researcher has collected the respondents' views using the five points Likert scale in survey among 303 respondents and 21 participants in focus group discussion. The researcher has explored the results to meet its stated objectives and corresponding research questions, and found meaningful. The triangulation of qualitative and quantitative analysis conducted separately on primary data collected. The qualitative analysis used respondents' idea, and experience collection and generalization. Whereas, quantitative analysis used hypothesis tests Man-Whitney Test and Kruskal Test and Descriptive Statistics. The results revealed the existence of 10 variables under qualitative determinants, and 13 variables under quantitative determinants respectively. Moreover, the researcher found that qualitative variables significantly effect the stock price under non-parametric tests conducted for the hypothesis testing for the assessment of the effect of the quantitative determinants found the relationship between the 13 quantitative variables with the stock price found as significant The approaches taken for the hypothesis testing were statistically accepted at a 5 per cent level of significance with perfectly stated value of p-value. Therefore, existing investors and potential investors all are to consider the determinants before making their investment in the stock market.